A review of the scope of farmer participatory research to inform breeding of root, tuber and banana crops - Valle, José Francisco; Arnaud, Elizabeth; Marimo, Pricilla; Etten, Jacob van (2022)
In order to assess the advances in participatory research for root, tuber and banana crops with focus on trait preferences, we have compiled available published and grey literature about Participatory Varietal Selection up to September 2020. Methodology: In total 123 entries in the database. Studies were characterized and priority traits were extracted and categorized. We performed a spatio-temporal analyse of the studies in research methodologies, gender inclusiveness and trait preferences across participatory research in cassava, banana, plantain, sweetpotato, yam and potato.